Quantum dot film patterning method and application

By using a photosensitive crosslinking agent containing electron-donating groups and the quantum dot surface ligand, efficient patterning of quantum dots in air is achieved, and the problem of difficulty in achieving efficient patterning in air in the prior art is solved. And maintain the photoelectric performance of quantum dots.

CN119497548AActive Publication Date: 2025-02-21TSINGHUA UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311027394.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-21
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

The existing quantum dot film patterning method is difficult to achieve efficient patterning in air, and it is harmful to the photoelectric performance of quantum dots, limiting its application in large-scale and low-cost production.

Method used

A photosensitive crosslinking agent containing electron donor groups is used to generate a singlet carbene intermediate by ultraviolet light irradiation, and react with carbon-hydrogen bond insertion of the quantum dot surface ligand to achieve crosslinking and patterning of quantum dots.

Benefits of technology

It realizes efficient patterning of quantum dots of different types and compositions in the air, with high resolution and strong universality, and is suitable for large-scale industrial production and does not damage the photoelectric performance of quantum dots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497548A_ABST
    Figure CN119497548A_ABST
Patent Text Reader

Abstract

The invention provides a quantum dot film patterning method and application. The quantum dot film patterning method comprises the following steps: (1) mixing quantum dots with a photosensitive cross-linking agent to form a thin layer; (2) carrying out patterning exposure treatment on the thin layer to obtain a patterned quantum dot thin film; wherein ligands containing carbon-hydrogen bonds are arranged on the surfaces of the quantum dots; the photosensitive cross-linking agent has a structure as shown in a formula I: # imgabs0 #, wherein R1 is an electron donating group; n > = 2; x is a group which does not affect generation of a singlet intermediate. The quantum dot film patterning method can realize efficient patterning of different types of formed quantum dots in the air, has the advantages of high resolution, strong universality and suitability for large-scale industrial production, can be used for preparing photoelectric devices such as quantum dot LEDs and the like, and can maintain the photoelectric property of the quantum dot material to a greater extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of optoelectronic technology, and in particular relates to a method for preparing a patterned quantum dot film and the construction of a light-emitting display device. Background Art

[0002] Quantum dots (QDs) are semiconductor nanocrystals with a size smaller than the Bohr radius, with a common size of 2-20nm. They are composed of an inorganic semiconductor core and surface ligands, and have obvious volume effect, surface effect, size effect and other characteristics. Their luminescent wavelength can be controlled and adjusted according to their size, with a narrow emission half-width and a wide color gamut. Compared with traditional semiconductor materials such as silicon, quantum dots can form stable colloidal solutions, and low-cost, large-area, and high-efficiency optoelectronic devices can be constructed by solution method.

[0003] In the field of optoelectronic devices, quantum dots are usually used as photoelectric active layers in the form of thin films. Patterning methods can achieve the construction of quantum dot arrays with micrometer-scale resolution, which has broader application prospects in the fields of high-definition and colorful flat-panel displays or lighting, sensor imaging, photoelectric stimulation, etc. Conventional quantum dot thin film patterning methods have defects. For example, photolithography technology is difficult to ensure the compatibility of quantum dots and photoresists, the pattern resolution achieved by inkjet printing technology is limited (>50 microns), and technologies such as electron beam or laser direct writing damage the photoelectric properties of quantum dots themselves.

[0004] In recent years, new patterning methods based on quantum dot surface chemistry can efficiently realize high-resolution (<5 microns) patterned quantum dot films. However, most of the methods reported so far are implemented under inert gas. When quantum dot patterning is performed in air, there may be problems such as failure to form patterns or reduction of the photoelectric performance of quantum dot films. CN114839835A uses photosensitive cross-linking molecules containing diazirine groups (i.e., carbene cross-linking molecules) to realize the patterning of quantum dot films. In a nitrogen environment, the singlet carbene intermediates generated by the cross-linking molecules undergo insertion reactions with the carbon-hydrogen bonds in the surface ligands of the quantum dots, thereby cross-linking the quantum dots to achieve patterning. However, the singlet carbene intermediates with higher energy (the net electron spin S in the molecule is 0) are easily converted to triplet states (the net electron spin S in the molecule is 1). When exposed to air, the triplet carbene produced reacts rapidly with oxygen in the air. This side reaction depletes the singlet carbene, and the quantum dots cannot be cross-linked to form patterns. In addition, the effect of air environment on the photoelectric properties of quantum dots during patterning is often overlooked, especially for III-V quantum dots without heavy metal components such as cadmium, whose photoelectric properties are more easily affected by factors such as oxygen. These problems restrict the actual development and application of quantum dot film patterning methods in large-scale, low-cost production. Therefore, it is urgent to develop a quantum dot film patterning method that can be implemented in air and does not damage the performance of quantum dots. Summary of the invention

[0005] In order to solve the above problems, the purpose of the present invention is to provide a quantum dot thin film patterning method and application, which can realize efficient patterning of quantum dots of different types and compositions in the air, and has the advantages of high resolution, strong universality, and suitability for large-scale industrial production.

[0006] In order to achieve the above object, the present invention provides a quantum dot thin film patterning method, which comprises the following steps:

[0007] (1) mixing quantum dots and a photosensitive crosslinker to form a thin layer; (2) performing patterned exposure treatment on the thin layer to obtain a patterned quantum dot film; wherein the surface of the quantum dots has a ligand containing a carbon-hydrogen bond; and the photosensitive crosslinker has a structure shown in Formula I:

[0008]

[0009] In formula I, R1 is an electron-donating group; n≥2; and X is a group that does not affect the formation of a singlet intermediate.

[0010] In Formula I, the photosensitive crosslinker loses N2 molecules under ultraviolet light to obtain a carbene intermediate containing an electrically neutral divalent carbon atom. During the exposure process, the singlet intermediate undergoes an insertion reaction with the carbon-hydrogen bond in the ligand on the surface of the quantum dot, so that the quantum dots are cross-linked with each other. X can be any functional group under the condition that it does not affect the generation of the intermediate; R1 is a group that can stabilize the singlet carbene intermediate in the air, and R1 is designed to be an electron-donating group (i.e., a group that exhibits a negative electric field to the outside, and the electron-donating group is a group that can increase the electron cloud density on the benzene ring when the substituent replaces the hydrogen on the benzene ring). The introduction of R1 is used to inhibit the conversion of the carbene intermediate from the singlet state to the triplet state, and to improve the stability of the singlet intermediate to oxygen in the air, so that the ligands in the exposure process are fully cross-linked.

[0011] According to a specific embodiment of the present invention, preferably, in Formula I, R1 contains one or more structures selected from the group consisting of alkylamino, alkoxy, ether, acyloxy, amide, alkyl, alkylene, carboxymethyl, and phenyl; n is 2, 3, or 4; and X is selected from the group consisting of H, halogen, hydroxyl, alkyl and its derivatives, alkoxy and its derivatives, amino, and nitrile.

[0012] According to a specific embodiment of the present invention, preferably, X is selected from -Cl, -F, -OH, -H, -CH3, -CF3, -OCH3, -NH2 or -CN, preferably -CF3, which is beneficial to improve the reaction activity.

[0013] According to a specific embodiment of the present invention, preferably, R1 contains one or more structures of phenyl, ether, and alkylene; n is 2, 3 or 4; and X is selected from -CF3.

[0014] According to a specific embodiment of the present invention, preferably, the photosensitive crosslinker has 1-100 carbon atoms and a molecular weight of 100-10000; in view of molecular safety and ease of synthesis, the molecular weight is more preferably 500-2000.

[0015] According to a specific embodiment of the present invention, preferably, the photosensitive crosslinking agent is selected from

[0016]

[0017] (1,3,5-tris((2-(3-(3-(trifluoromethyl)-3H-diazirin-3-yl)phenoxy)ethoxy)methyl)benzene, photosensitive crosslinker A),

[0018]

[0019] (3-(trifluoromethyl)-3-(3-(2-((4-((2-(4-(3-(trifluoromethyl))-3H-diazirin-3-yl)phenoxy)ethoxy)methyl)benzyl)oxy)ethoxy)phenyl)-3H-diazirine, photosensitive cross-linking agent B),

[0020]

[0021] (bis(4-(3-(trifluoromethyl)-3H-diazirin-3-yl)phenoxy)octane, photosensitive crosslinker C),

[0022]

[0023] (1,2,4,5-tetrakis((2-(3-(3-(trifluoromethyl)-3H-diazirin-3-yl)phenoxy)ethoxy)methyl)benzene, photosensitive crosslinker D) or a combination of two or more thereof.

[0024] According to a specific embodiment of the present invention, preferably, the material of the quantum dots (the material of single-component quantum dots, the material of the core or shell of core-shell quantum dots) includes one or a combination of two or more of Group II-VI compounds, Group III-V compounds, Group IV-VI compounds, Group I-III-VI compounds, and perovskite nanocrystals.

[0025] According to a specific embodiment of the present invention, preferably, the quantum dots are quantum dots with a core-shell structure.

[0026] According to a specific embodiment of the present invention, preferably, the II-VI group compound includes CdSe, CdS, CdTe, Cd x Se 1-x S, Cd x Se 1-x Te, ZnO, ZnSe, ZnS, ZnTe, Zn x Se 1-x S, Zn x Se 1-x Te, Cd x Zn 1-x Se, Cd x Zn 1-x S, Cd x Zn 1-x Te, HgSe, HgS, HgTe, Hg x Cd 1-x Se, Hg x Cd 1-x S, Hg x Cd 1-x One or a combination of two or more of Te, wherein 0<x<1.

[0027] According to a specific embodiment of the present invention, preferably, the III-V group compound includes one or a combination of two or more of InP, InAs, InSb, InN, GaP, GaAs, GaSb, GaN, AlP, AlAs, AlSb, and AlN.

[0028] According to a specific embodiment of the present invention, preferably, the IV-VI group compound includes PbS, PbSe, PbTe, Pb x Se 1-x S, Pb x Se 1-x Te, SnS, SnSe, SnTe, Sn x Se 1-x S, Sn x Se 1-x One or a combination of two or more of Te, wherein 0<x<1.

[0029] According to a specific embodiment of the present invention, preferably, the I-III-VI group compound includes one or a combination of two or more of CuInS2, CuInSe2, and AgInS2.

[0030] According to a specific embodiment of the present invention, preferably, the perovskite nanocrystals include one or a combination of two or more of CsPbY3, CH3NH3PbY3, FAPbY3, MAPbY3, wherein Y is selected from Cl, Br or I, and MA and FA represent methylammonium and formamide, respectively.

[0031] According to a specific embodiment of the present invention, preferably, the number of carbon atoms of the surface ligands of the quantum dots is 3-30.

[0032] According to a specific embodiment of the present invention, preferably, the surface ligands of the quantum dots contain hydrocarbon chains.

[0033] According to a specific embodiment of the present invention, preferably, the main chain of the surface ligand of the quantum dot contains a carbon-hydrogen bond.

[0034] According to a specific embodiment of the present invention, preferably, the surface ligands of the quantum dots contain one or more structures of thiol, carboxylic acid, amine, phosphine, and phosphonic acid.

[0035] According to a specific embodiment of the present invention, preferably, the surface ligands of the quantum dots include one or a combination of two or more of oleylamine, oleic acid, octadecylamine, 1-dodecanethiol, trioctylphosphine, and octadecylphosphonic acid.

[0036] According to a specific embodiment of the present invention, preferably, in step (1), quantum dots and a photosensitive crosslinker are mixed in a solvent to obtain a solution, and the solution is formed into a thin layer; wherein the concentration of quantum dots in the solution is 5-1000 mg / ml, and the mass concentration ratio of quantum dots to the added photosensitive crosslinker is 1:(0.01-1).

[0037] According to a specific embodiment of the present invention, preferably, the solvent of the solution is selected from one or a combination of two or more of toluene, chlorobenzene, n-hexane, n-octane, n-heptane, cyclohexane, dichloromethane, chloroform and tetrahydrofuran.

[0038] According to a specific embodiment of the present invention, preferably, the molar absorption coefficient of the photosensitive crosslinking agent at the exposure treatment wavelength is 10 cm -1 M -1 Up to 10 6 cm -1 M -1 .

[0039] According to a specific embodiment of the present invention, preferably, each step of the quantum dot thin film patterning method is implemented in air, nitrogen, argon or other inert gases.

[0040] According to a specific embodiment of the present invention, preferably, in step (2), the wavelength of the exposure treatment is 100-500nm (more preferably 200-500nm), and the light dose is 1-5000mJ / cm 2 .

[0041] According to a specific embodiment of the present invention, preferably, after the thin layer is exposed, an elution solvent is used to remove the raw material that has not undergone cross-linking (remove the unexposed quantum dot area), and the elution solvent is a non-polar solvent (dielectric constant is less than 10), more preferably including one or a combination of more than two of toluene, chlorobenzene, n-hexane, n-octane, n-heptane, cyclohexane, dichloromethane, chloroform, and tetrahydrofuran.

[0042] According to a specific embodiment of the present invention, the above method comprises the following specific steps:

[0043] (1) forming a thin film layer in which quantum dots and a photosensitive crosslinking agent are uniformly dispersed on one side of the substrate;

[0044] (2) performing an exposure treatment on a specific area of ​​the quantum dot thin film layer, so that a ligand cross-linking reaction occurs in the exposed part;

[0045] (3) Then, the unexposed portion is removed by solvent washing to obtain a patterned quantum dot film.

[0046] The present invention also provides a patterned quantum dot film prepared by the above-mentioned quantum dot film patterning method.

[0047] The present invention also provides a photoelectric device, whose structural composition includes an anode, a cathode, and a quantum dot light-emitting layer, wherein the quantum dot light-emitting layer is the above-mentioned patterned quantum dot film or is prepared by the above-mentioned quantum dot film patterning method.

[0048] According to a specific embodiment of the present invention, preferably, the quantum dot light-emitting layer is located between the cathode and the anode, and the materials of the anode and the cathode are independently selected from metals or carbon materials; the metal is selected from one or a combination of two or more of Al, Ag, Au, Cu, Mo, Mg, Ba, and Ca, and the carbon material is selected from one or a combination of two or more of carbon nanotubes, graphite, graphene, and carbon fibers.

[0049] According to a specific embodiment of the present invention, preferably, the structure of the optoelectronic device further comprises an electron injection layer, a hole injection layer, an electron transport layer and a hole transport layer, wherein the electron injection layer and the electron transport layer are located between the cathode and the quantum dot light-emitting layer, the electron injection layer is close to the cathode side, and the electron transport layer is close to the quantum dot light-emitting layer; the hole injection layer and the hole transport layer are located between the anode and the quantum dot light-emitting layer, the hole injection layer is close to the anode side, and the hole transport layer is close to the quantum dot light-emitting layer side.

[0050] According to a specific embodiment of the present invention, preferably, the material of the electron injection layer includes one or a combination of two or more of alkali metal halides, alkali metal organic complexes, organic phosphorus oxides, and organic thio (or seleno) phosphine compounds.

[0051] According to a specific embodiment of the present invention, preferably, the material of the electron transport layer includes a single metal oxide and / or a doped metal oxide, and the single metal oxide is selected from one or a combination of more than two of ZnO, ZrO2, SnO2, BaO, TiO2, Ta2O3; the doped metal oxide is the above-mentioned single metal oxide doped with a certain proportion of one or more elements selected from Al, Li, Ga, Mg, Sn, In, F, Cl, etc.

[0052] According to a specific embodiment of the present invention, preferably, the material of the hole injection layer is selected from poly(3,4-ethylenedioxythiophene), poly(styrenesulfonic acid), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, 4,4',4'-tri(2-naphthylphenylamino)triphenylamine, 1,4,5,8,9,12-hexaazatriphenyl-2,3,6,7,10,11-hexanitrile, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, metal oxides such as NiO, MoO2, WO3, CrO3, CuO, and transition metal sulfur compounds such as MoS2, MoSe2, WS2, CuS, WS2, or a combination of more than two thereof.

[0053] According to a specific embodiment of the present invention, preferably, the material of the hole transport layer is selected from poly(3-hexylthiophene-2,5-diyl), poly(9-vinylcarbazole), poly[[(2,4-dimethylphenyl)imino]-1,4-phenylene(9,9-dioctyl-9H-fluorene-2,7-diyl)-1,4-phenylene], poly(9,9-dioctylfluorene-2,7-diyl), poly[bis(4-phenyl)(4-butylphenyl)amine], poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-tert-butylphenyl)diphenylamine)], poly[9, 9-dioctylfluorene-bis-N,N-(4-butylphenyl)-bis-N,N-phenyl-1,4-phenylenediamine], tris[4-(carbazole-9-yl)phenyl]amine, 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, poly(3,4-ethylenedioxythiophene), poly(styrenesulfonic acid), graphene, NiO, WO3, CuI, CuSCN, CuO, CuInS2, GaN, C60, MoO3, V2O5, CrO3, or a combination of two or more thereof.

[0054] According to a specific embodiment of the present invention, preferably, the above-mentioned optoelectronic device is an array optoelectronic device.

[0055] The present invention provides a quantum dot patterning method that can be implemented in air and does not damage the photoelectric properties of quantum dots through the chemical design of cross-linked molecules. Electron-donating groups are introduced into carbene cross-linked molecules to make the energy of singlet carbene intermediates significantly lower than that of triplet states. In air, singlet carbene does not convert to triplet states to react with oxygen, but can realize quantum dot film patterning by cross-linking quantum dot surface ligands. The present invention has the following beneficial effects:

[0056] 1. This method is not only feasible in an inert gas atmosphere such as nitrogen and argon, but can also achieve efficient patterning of quantum dot materials of different types and compositions in air. The resulting pattern resolution can reach 2 microns, which is close to the limit resolution of the UV lithography machine used. The operation is simple and easy, and is suitable for low-cost, large-scale actual production and application;

[0057] 2. Under air conditions, the designed carbene singlet intermediates are stable, the cross-linking reaction is mild, and the optical properties of different types of quantum dots are not damaged;

[0058] 3. The method for constructing the light-emitting layer of the quantum dot light-emitting display device provided by the present invention can be applied to actual QLEDs (quantum dot light-emitting diodes), and exhibits a level comparable to that of ordinary thin-film devices in terms of luminous brightness and current density, and can maintain the electrical properties of the quantum dot material itself. The efficient and stable patterning method in the air has opened up an important path for the development of full-color light-emitting displays based on quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a diagram of the cross-linking mechanism between quantum dots and carbene cross-linkers;

[0060] Figure 2 A schematic diagram of the process of patterning quantum dot films;

[0061] Figure 3 These are optical photographs of cadmium-free quantum dot patterns with three different luminescent colors based on the photosensitive crosslinker A in Example 1 under a fluorescence microscope;

[0062] Figure 4 This is an optical photograph of a ZnSe / ZnS quantum dot pattern with different ligands based on the photosensitive crosslinker A in Example 2 under a fluorescence microscope;

[0063] Figure 5 This is an optical photograph of a lnP / ZnS quantum dot pattern under a fluorescence microscope based on the photosensitive crosslinker B in Example 3;

[0064] Figure 6 This is an optical photograph of a lnP / ZnS quantum dot pattern under a fluorescence microscope based on the photosensitive crosslinker C in Example 4;

[0065] Figure 7 These are optical photographs of cadmium-based quantum dot patterns with three different luminescent colors based on the photosensitive crosslinker A in Example 5 under a fluorescence microscope;

[0066] Figure 8 In Example 6, based on photosensitive crosslinking agents B and C, a cadmium-based CdSe / Cd 1-x Zn x Optical photograph of Se / ZnSe quantum dot pattern under fluorescence microscope;

[0067] Fig. 9 These are optical photographs of three quantum dot multicolor patterns in Example 7 under a fluorescence microscope;

[0068] Fig.10 The molar absorption coefficient diagram of three photosensitive crosslinking agents A, B, and C;

[0069] Fig.11 The graphs of fluorescence quantum yield changes of two different color lnP / ZnS quantum dot films before and after patterning;

[0070] Fig.12 This is a graph showing the fluorescence lifetime change of a lnP / ZnS quantum dot film before and after patterning;

[0071] Fig.13 It is a cadmium-based CdSe / Cd 1-x Zn x Fluorescence quantum yield change diagram of Se / ZnSe quantum dot film before and after patterning;

[0072] Fig.14 The diagrams of constructed cadmium-based and InP-based QLEDs devices, wherein A is a diagram of the specific structure of cadmium-based and InP-based QLEDs, B is a photo of the electroluminescent pattern of cadmium-based QLEDs, C is a diagram of the relationship between current density and luminous brightness and voltage of cadmium-based QLEDs, D is a diagram of the luminous wavelength of cadmium-based QLEDs at different voltages and a diagram of the unit pixel of the QLEDs actually lit up in the test, E is a diagram of the relationship between current density and luminous brightness and voltage of InP-based QLEDs, and F is a diagram of the luminous wavelength of InP-based QLEDs at different voltages;

[0073] Fig.15 This is a graph showing the change in fluorescence quantum yield of a lnP / ZnS quantum dot film before and after patterning;

[0074] Fig.16 This is a graph showing the fluorescence lifetime change of a lnP / ZnS quantum dot film before and after patterning;

[0075] Fig.17 This is a photo of the effect of lnP / ZnS quantum dot patterning under a fluorescence microscope;

[0076] Fig.18 This is a photo of the effect of lnP / ZnS quantum dot patterning under a fluorescence microscope. DETAILED DESCRIPTION

[0077] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0078] Preparation Example 1

[0079] This preparation example provides a photosensitive crosslinker molecule A, and its synthesis method is as follows (refer to patent PCT / CA2022 / 050293):

[0080] Under argon atmosphere, NaH (60% dispersion in mineral oil, 632 mg) was added to anhydrous tetrahydrofuran (10 mL), and an anhydrous tetrahydrofuran solution (5 mL) of 2-(4-(3-(trifluoromethyl)-3H-diacridin-3-yl)phenoxy)ethane-1-ol (3.26 g) was added dropwise at 0°C, and the reaction was stirred for 10 minutes. Then, an anhydrous tetrahydrofuran solution (10 mL) of 1,3,5-tri(bromomethyl)benzene (1.52 g) was added dropwise at 0°C, and the reactants were stirred at room temperature overnight. The colored mixture was filtered and washed with a dichloromethane solution, and purified by silica gel column chromatography using hexane and dichloromethane as eluents to obtain a yellow oily photosensitive crosslinker A.

[0081] Preparation Example 2

[0082] This preparation example provides a photosensitive crosslinker molecule B, and its synthesis method is as follows (refer to patent PCT / CA2022 / 050293):

[0083] Under argon atmosphere, NaH (60% dispersion in mineral oil, 1.68 g) was added to anhydrous tetrahydrofuran (30 mL), and an anhydrous tetrahydrofuran solution (15 mL) of 2-(4-(3-(trifluoromethyl)-3H-diacridin-3-yl)phenoxy)ethane-1-ol (8.28 g) was added dropwise at 0°C, and the reaction was stirred for 10 minutes. Then, anhydrous tetrahydrofuran (20 mL) of 1,4-bis(bromomethyl)benzene (4.44 g) was added dropwise at 0°C, and the reactants were stirred at room temperature overnight. The colored mixture was filtered and washed with dichloromethane, and further purified by silica gel column chromatography using pentane and diethyl ether as eluents to obtain photosensitive crosslinker B.

[0084] Preparation Example 3

[0085] This preparation example provides a photosensitive crosslinker molecule C, and its synthesis method is as follows (refer to the literature "Stefania F. Musolino, et al. Structure-function relationships in aryl diazirines reveal optimal design features to maximize C-H insertion, Chem. Sci., 2021, 12, 12138-12148"):

[0086] Triethylamine (6.8 mL) and iodine (4.52 g) were added to a dichloromethane solution (41 mL) of 1,8-bis(4-(3-(trifluoromethyl)diazetidine-3-yl)phenoxy)octane (4.2 g) at 0°C. The colored mixture was stirred at 0°C for 1 hour, diluted with a dichloromethane solution, and washed with a saturated aqueous sodium thiosulfate solution. The organic extract was washed with brine after extraction with a dichloromethane solution three times, dried with magnesium sulfate, filtered and concentrated, and the product was purified by silica gel column chromatography using pentane and ether as eluents to obtain a light yellow solid photosensitive crosslinker C.

[0087] Preparation Example 4

[0088] This preparation example provides a photosensitive crosslinker molecule D, and its synthesis method is as follows (refer to patent PCT / CA2022 / 050293):

[0089] Under argon atmosphere, NaH (60% dispersion in mineral oil, 632 mg) was added to anhydrous tetrahydrofuran (30 mL), and an anhydrous tetrahydrofuran solution (15 mL) of 2-(4-(3-(trifluoromethyl)-3H-diacridin-3-yl)phenoxy)ethane-1-ol (3.26 g) was added dropwise at 0°C, and the reaction was stirred for 10 minutes. Then, an anhydrous tetrahydrofuran solution (20 mL) of 1,2,4,5-tetra(bromomethyl)benzene was added dropwise at 0°C, and the reactants were stirred at room temperature overnight. The colored mixture was filtered, washed, and purified by silica gel column chromatography to obtain a yellow oily photosensitive crosslinker D.

[0090] Example 1

[0091] This embodiment provides a quantum dot patterning method based on photosensitive crosslinker molecule A and three cadmium-free quantum dot patterned films; wherein the quantum dots used for patterning include red and green lnP (core) / ZnS (shell) quantum dots, and the surface ligands are mainly oleic acid. Reference for the synthesis of red and green quantum dots (Bing Chen, et al. InP Quantum Dots: Synthesis and Lighting Applications, Small, 2020, 16, 2002454); including ZnSe (core) / ZnS (shell) blue quantum dots, the surface ligands are mainly oleylamine and oleic acid, and the blue quantum dot synthesis reference (Min Gao, et al. Bulk-like ZnSe Quantum Dots Enabling Efficient Ultra-narrow Blue Light-Emitting Diodes, Nano Lett., 2021, 21, 7252-7260). The specific implementation steps are as follows:

[0092] (1) In an air atmosphere, take a silicon wafer as a substrate, and use organic solvents such as toluene, acetone, methanol, and isopropanol to ultrasonically clean it for 15 minutes respectively; spin-coat a solution of quantum dots of a certain color and photosensitive crosslinker A on one side of the silicon wafer at a speed of 1500 rpm, and the solvent is toluene. For red quantum dots, the concentration of lnP / ZnS red quantum dots in the solution is 30 mg / mL, and the concentration of photosensitive crosslinker A is 1 mg / mL; for green quantum dots, the concentration of lnP / ZnS green quantum dots in the solution is 30 mg / mL, and the concentration of photosensitive crosslinker A is 2 mg / mL; for blue quantum dots, the concentration of ZnSe / ZnS blue quantum dots in the solution is 20 mg / mL, and the concentration of photosensitive crosslinker A is 1 mg / mL;

[0093] (2) Selectively expose a quantum dot film of one color using a mask. The exposure light source is 365 nm and the light dose is 50 mJ / cm 2 , the illumination time is 5s, the photosensitive crosslinker A in the exposed part crosslinks with the oleylamine or oleic acid ligand on the surface of the quantum dots, changing the solubility of the quantum dots in toluene, which is different from the unexposed part;

[0094] (3) The quantum dot film is immersed in toluene, and the quantum dots in the unexposed part fall off the silicon wafer, while the pattern appears in the selectively exposed part.

[0095] The crosslinking mechanism between quantum dots and carbene crosslinking agents in the quantum dot patterning method of the present invention is as follows: Figure 1 As shown in Figure 2, the process of patterning quantum dot thin films is as follows: Figure 2 shown.

[0096] The optical microscope photos of the red, green and blue patterns prepared in this embodiment are shown in FIG. Figure 3 As shown, Figure 3 A in the middle is a red quantum dot circular array pattern, and the diameter of the circle is 30 microns; Figure 3 Middle B is an “animal dog” pattern formed by green quantum dots; Figure 3 The "Tsinghua University emblem" pattern formed by blue quantum dots is shown in the middle C, demonstrating the ability of this method to construct complex patterns.

[0097] Example 2

[0098] This embodiment provides a quantum dot patterning method based on a photosensitive crosslinker A and a patterned film of quantum dots with different ligands. The quantum dots used in this embodiment are ZnSe / ZnS blue quantum dots, the surface ligands are mainly 1-dodecanethiol, and the preparation method of quantum dots is referred to the literature Jeehye Yang, et al. Nondestructive Photopatterning of Heavy-Metal-Free Quantum Dots, Adv. Mater., 2022, 34, 2205504.

[0099] Compared with the preparation method of the blue ZnSe / ZnS quantum dot patterned film in Example 1, the difference between this embodiment and Example 1 is that the surface ligands of ZnSe / ZnS blue quantum dots, oleylamine and oleic acid, are replaced with 1-dodecanethiol to obtain Figure 4 A blue quantum dot array with a line width of 2 microns is shown.

[0100] Example 3

[0101] This embodiment provides a quantum dot patterning method based on a photosensitive crosslinker B and a quantum dot patterned film. The selected InP / ZnS red quantum dots are the same as those in Example 1, and the surface ligand is oleylamine or oleic acid. The specific implementation steps are as follows:

[0102] (1) In an air atmosphere, a commercial silicon wafer was used as a substrate and ultrasonically cleaned for 15 minutes using organic solvents such as toluene, acetone, methanol, and isopropanol. A solution of red lnP / ZnS quantum dots and photosensitive crosslinker B was spin-coated on one side of the silicon wafer at a speed of 1500 rpm. The solvent was toluene. The concentration of the lnP / ZnS red quantum dots in the solution was 30 mg / mL, and the concentration of the photosensitive crosslinker B was 2 mg / mL.

[0103] (2) The red quantum dot film was selectively exposed using a mask in an air atmosphere with an exposure light source of 365 nm and a light dose of 200 mJ / cm 2 , the illumination time is 20s, the photosensitive crosslinker B in the exposed part cross-links with the ligands on the surface of the quantum dots, changing the solubility of the red quantum dots in toluene, which is different from the unexposed part;

[0104] (3) The quantum dot film is immersed in toluene, and the unexposed part of the quantum dots falls off the silicon wafer, while the selectively exposed part shows the following Figure 5 The red quantum dot diamond array pattern shown has a diamond side length of 50 microns.

[0105] Example 4

[0106] This embodiment provides a quantum dot patterning method based on a photosensitive crosslinker C and a quantum dot patterned film. The same InP / ZnS red quantum dots as in Example 1 are selected. The specific implementation steps are as follows:

[0107] (1) In an air atmosphere, a commercial silicon wafer was used as a substrate and ultrasonically cleaned for 15 minutes using organic solvents such as toluene, acetone, methanol, and isopropanol. A solution of red lnP / ZnS quantum dots and photosensitive crosslinker C was spin-coated on one side of the silicon wafer at a speed of 1500 rpm. The solvent was toluene. The concentration of the lnP / ZnS red quantum dots in the solution was 30 mg / mL, and the concentration of the photosensitive crosslinker C was 2 mg / mL.

[0108] (2) The red quantum dot film was selectively exposed using a mask in an air atmosphere with an exposure light source of 365 nm and a light dose of 300 mJ / cm 2 , the illumination time is 30s, the photosensitive crosslinker C in the exposed part cross-links with the ligands on the surface of the quantum dots, changing the solubility of the red quantum dots in toluene, which is different from the unexposed part;

[0109] (3) The quantum dot film is immersed in toluene, and the unexposed part of the quantum dots falls off the silicon wafer, while the selectively exposed part shows the following Figure 6 The red quantum dot square array pattern shown has a side length of 60 microns.

[0110] Example 5

[0111] This embodiment provides a quantum dot patterning method based on photosensitive crosslinker A and three cadmium-based quantum dot patterned films. Cadmium-based red quantum dots CdSe / CdS are selected, and the surface ligand is oleylamine. The preparation method is based on the literature (Chaodan Pu, et al. Electrochemically-stable ligands bridge the photoluminescence-electroluminescence gap of quantum dots. Nat. Commun., 2020, 11(1): 937). Cadmium-based green quantum dots CdSe / CdS are selected. 1-x Zn x Se 1-y S y / ZnS, the surface ligand is oleic acid, the preparation method of the quantum dots is referenced (Himchan Cho, et al. Direct Optical Patterning of Quantum Dot Light-Emitting Diodes via In Situ Ligand Exchange. Adv. Mater., 2020, 32, 2003805), and the cadmium-based blue quantum dots Cd 1-x Zn x S / ZnS, the surface ligand is oleic acid. Quantum dot preparation method reference (Wan Ki Bae, et al. Gram-Scale One-Pot Synthesis of Highly Luminescent Blue Emitting Cd 1-x Zn x S / ZnS Nanocrystals. Chem. Mater., 2008, 20, 5307–5313). The specific implementation steps are as follows:

[0112] (1) In air, a commercial silicon wafer was used as a substrate and ultrasonically cleaned for 15 minutes using organic solvents such as toluene, acetone, methanol, and isopropanol. A solution of cadmium-based quantum dots and photosensitive crosslinker A was spin-coated on one side of the silicon wafer at a speed of 1500 rpm. The solvent was toluene. For red quantum dots, the concentration of CdSe / CdS red quantum dots in the solution was 30 mg / mL, and the concentration of photosensitive crosslinker A was 1 mg / mL. For green quantum dots, the concentration of CdSe / CdS red quantum dots in the solution was 100 mg / mL. 1-x Zn x Se 1-y S y / ZnS quantum dots concentration was 30mg / mL, and the concentration of photosensitive crosslinker A was 2mg / mL; for blue quantum dots, Cd 1-x Zn x The concentration of S / ZnS blue quantum dots was 20 mg / mL, and the concentration of photosensitive crosslinker A was 1 mg / mL;

[0113] (2) The cadmium-based quantum dot film was selectively exposed using a mask in an air atmosphere with an exposure light source of 365 nm and a light dose of 50 mJ / cm 2 , the illumination time is 5s, the photosensitive crosslinker A in the exposed part cross-links with the ligands on the surface of the quantum dots, changing the solubility of the quantum dots in toluene, which is different from the unexposed part;

[0114] (3) The quantum dot film is immersed in toluene, and the unexposed part of the quantum dots falls off the silicon wafer, while the selectively exposed part shows the following Figure 7 The pattern shown. Figure 7 A to C in the figure are red, green, and blue patterns respectively;

[0115] Example 6

[0116] This embodiment provides a quantum dot patterning method based on photosensitive crosslinkers B and C and a cadmium-based quantum dot patterned film. 1-x Zn x Se / ZnSe red quantum dots, the ligand is mainly oleic acid, and the quantum dot preparation method refers to "Chaoyu Xiang, et al. High efficiency and stability of ink-jet printed quantum dot light emitting diodes. Nat Commun., 2020, 11 (1): 1646". The specific patterning implementation steps are the same as those in Example 5. The patterning effect diagram is shown in FIG. Figure 8 As shown, Figure 8 A is a red quantum dot array with a line width of 50 microns obtained based on photosensitive crosslinker B. During the implementation process, the concentration of quantum dots in the solution was 30 mg / mL, the concentration of photosensitive crosslinker B was 1 mg / mL, and the light dose was 200 mJ / cm 2 , Figure 8 Figure B is a red quantum dot array with a line width of 10 microns obtained based on photosensitive crosslinker C. During the implementation process, the concentration of quantum dots in the solution was 30 mg / mL, the concentration of photosensitive crosslinker C was 1 mg / mL, and the light dose was 300 mJ / cm 2 .

[0117] Example 7

[0118] This embodiment provides a quantum dot patterning method based on photosensitive crosslinker A and a multicolor patterned film of three-color quantum dots. The selected red, green, and blue quantum dots are the same as those in Example 1. The specific implementation steps are as follows:

[0119] (1) In an air atmosphere, a commercial silicon wafer was used as a substrate and ultrasonically cleaned for 15 minutes using organic solvents such as toluene, acetone, methanol, and isopropanol; a solution of red lnP / ZnS quantum dots and photosensitive crosslinker A was first spin-coated on one side of the silicon wafer at a speed of 1500 rpm, wherein the solvent was toluene, the concentration of the lnP / ZnS red quantum dots in the solution was 30 mg / mL, and the concentration of the photosensitive crosslinker A was 1 mg / mL;

[0120] (3) The red quantum dot film was selectively exposed using a mask. The exposure light source was 365 nm and the light dose was 100 mJ / cm 2 , illumination time 10s;

[0121] (3) immersing the quantum dot film in toluene, causing the unexposed quantum dots to fall off the silicon wafer and the selectively exposed portions to appear, thereby obtaining a red array pattern that is no longer soluble in toluene;

[0122] (4) On the substrate showing the red pattern, continue to spin-coat a solution of green lnP / ZnS quantum dots and photosensitive crosslinker A at 1500 rpm, the solvent is toluene, the concentration of lnP / ZnS green quantum dots in the solution is 30 mg / mL, and the concentration of photosensitive crosslinker A is 2 mg / mL;

[0123] (5) The green quantum dot film was selectively exposed using a mask, with an exposure light source of 365 nm and an exposure dose of 100 mJ / cm 2 , illumination time 10s;

[0124] (6) Soaking the quantum dot film in toluene, the unexposed quantum dots fall off the silicon wafer, and the selectively exposed green parts appear;

[0125] (7) On the substrate showing the red and green array patterns, continue to spin-coat a solution of blue ZnSe / ZnS quantum dots and photosensitive crosslinker A at 1000 rpm, the solvent is toluene, the concentration of ZnSe / ZnS blue quantum dots in the solution is 40 mg / mL, and the concentration of photosensitive crosslinker A is 2 mg / mL;

[0126] (8) The blue quantum dot film was selectively exposed using a mask, with an exposure light source of 365 nm and an exposure dose of 100 mJ / cm 2 , illumination time 10s;

[0127] (9) The quantum dot film is immersed in toluene, and the unexposed blue quantum dots fall off the silicon wafer, and the selectively exposed blue part appears, parallel to the previously cross-linked red and green array patterns, as shown in FIG. Fig. 9 As shown, the size of a single array is 10 microns by 50 microns.

[0128] Test Example 1 Determination of the molar absorption coefficient of photosensitive cross-linking molecules

[0129] This test example provides the molar absorption coefficient curves of three photosensitive crosslinking agents A, B, and C, such as Fig.10 As shown, the three photosensitive crosslinkers are configured with about 6×10 -4mol / L solution, the solvent is toluene, and the corresponding ultraviolet absorbance A is tested using Cary 5000 UV-Vis-NIR spectrometer. The molar absorption coefficient K is calculated using the Lambert-Beer law A=Kbc, where c is the concentration of the photosensitive crosslinker in mol / L, and b is the thickness of the absorption layer 1 cm. Referring to this method, the molar absorption coefficients of the three photosensitive crosslinkers in the ultraviolet band are obtained in turn, and the absorption capacity of the three photosensitive crosslinkers in the ultraviolet band is quantified.

[0130] Test Example 2 Comparison of fluorescence quantum yield before and after quantum dot patterning

[0131] This test example compares the fluorescence quantum yields of cadmium-free red and green quantum dots before and after patterning. The samples were prepared in air, and the selected InP / ZnS red quantum dots and InP / ZnS green quantum dots were the same as those in Example 1. The specific implementation steps are as follows:

[0132] (1) A red quantum dot solution was spin-coated on a 2 cm × 2 cm quartz sheet at a speed of 1500 rpm. The solvent was toluene. The concentration of the lnP / ZnS red quantum dots in the solution was 30 mg / mL. The fluorescence quantum yield of the film that was not subjected to the patterning step was measured using a Horiba FluoroMax Plus spectrometer.

[0133] (2) On a 2 cm × 2 cm quartz sheet, a solution of red quantum dots and photosensitive crosslinker A was spin-coated at a speed of 1500 rpm. The solvent was toluene. The concentration of lnP / ZnS red quantum dots in the solution was 30 mg / mL, and the concentration of photosensitive crosslinker A was 1 mg / mL. The fluorescence quantum yield of the film was tested using a Horiba FluoroMax Plus spectrometer.

[0134] (3) The film prepared according to the method of step (2) was subjected to ultraviolet exposure, with a wavelength of 365 nm and a light dose of 200 mJ / cm 2 , the illumination time was 20 s, and the fluorescence quantum yield of the film after the exposure step was tested using a Horiba FluoroMax Plus spectrometer;

[0135] (4) The exposed film was immersed in toluene solvent for elution, the film surface was dried with nitrogen, and the fluorescence quantum yield of the film after the elution step was tested using a Horiba FluoroMax Plus spectrometer;

[0136] Similarly, for green lnP / ZnS quantum dots, the luminescence quantum yield of the film after each patterning step was tested. The concentration of green quantum dots in the spin coating solution was 30 mg / mL, the concentration of photosensitive crosslinker A was 2 mg / mL, the illumination wavelength was 365 nm, and the illumination dose was 200 mJ / cm2 , illumination time 20s.

[0137] The results are as follows Fig.11 As shown, both red and green lnP / ZnS quantum dots can maintain good fluorescence quantum yield. The quantum yield of the initial film without treatment of quantum dots is normalized to 100%. After patterning in air, both red and green lnP / ZnS quantum dots have 90% fluorescence quantum yield retention.

[0138] Test Example 3: Changes in fluorescence lifetime before and after quantum dot patterning

[0139] This test example examines the change in fluorescence lifetime before and after quantum dot patterning, prepares samples in air, and selects the InP / ZnS red quantum dots in Example 1. The specific implementation steps are as follows:

[0140] (1) A 2 cm × 2 cm quartz sheet was also selected as the substrate, and a lnP / ZnS red quantum dot solution was spin-coated at a speed of 1500 rpm. The solvent was toluene, and the concentration of lnP / ZnS red quantum dots in the solution was 30 mg / mL. The average fluorescence lifetime of the film that was not subjected to the patterning step was tested using the Horiba FluoroMaxPlus with time-correlated single photon counting (TCSPC) system;

[0141] (2) A 2 cm × 2 cm quartz sheet was selected and a solution of red quantum dots and photosensitive crosslinker A was spin-coated at a speed of 1500 rpm. The solvent was toluene. The concentration of lnP / ZnS red quantum dots in the solution was 30 mg / mL, and the concentration of photosensitive crosslinker A was 1 mg / mL. The average fluorescence lifetime of the film was tested using the Horiba FluoroMax Plus with time-correlated single photon counting (TCSPC) system.

[0142] (3) The film obtained in step (2) was subjected to ultraviolet exposure at a wavelength of 365 nm and a light dose of 200 mJ / cm 2 The illumination time was 20 s, and the average fluorescence lifetime of the film after the exposure step was measured using the Horiba FluoroMax Plus with time-correlated single photoncounting (TCSPC) system;

[0143] (4) The exposed film was immersed in toluene solvent for elution, the film surface was dried with nitrogen, and the average fluorescence lifetime of the film after the elution step was measured using the Horiba FluoroMax Plus with time-correlated single photon counting (TCSPC) system;

[0144] The results are as follows Fig.12 As shown, the red lnP / ZnS quantum dots can maintain a good average fluorescence lifetime after patterning. The average fluorescence lifetime of the initial film without quantum dots treatment is 31.12ns. After mixing to form a quantum dot and photosensitive crosslinker film, the average fluorescence lifetime is 31.00ns. After UV exposure, the average fluorescence lifetime of the film is 28.98ns. After elution, the average fluorescence lifetime of the film is 30.59ns.

[0145] Test Example 4 Comparison of Fluorescence Quantum Yields Before and After Cadmium-Based Quantum Dot Patterning

[0146] This test example compares the fluorescence quantum yield of a cadmium-based quantum dot before and after patterning. The results are as follows: Fig.13 As shown, the quantum dots are selected from the red CdSe / Cd 1-x Zn x Se / ZnSe quantum dots, the specific implementation steps are the same as those of the red InP / ZnS quantum dots in Test Example 2. After patterning in air, the red CdSe / Cd 1-x Zn x The Se / ZnSe QDs have 80% fluorescence yield retention compared to the initial film.

[0147] Test Example 5 Construction of patterned cadmium-based QLEDs light-emitting display device and evaluation of corresponding electrical properties

[0148] This test example provides a construction of a patterned cadmium-based QLEDs light-emitting display device and the corresponding electrical performance evaluation. The CdSe / Cd 1-x Zn xSe / ZnSe red quantum dots, light-emitting display devices refer to the ITO / poly(3,4-ethylenedioxythiophene)polystyrene sulfonate(PEDOT:PSS) / Poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt(4,4'-(N-(4-butylphenyl)))](TFB) / Q Ds / ZnO / Al structure provided in the literature ChaoyuXiang,et al.High efficiency and stability of ink-jet printed quantum dotlight emitting diodes.Nat Commun.,2020,11(1):1646, such as Fig.14 As shown in A. The specific implementation steps are as follows:

[0149] (1) Take a clean ITO substrate, use commercial glass alkaline detergent to ultrasonically clean it for 15 minutes, then use deionized water to ultrasonically clean it for 15 minutes, repeat twice, then use anhydrous ethanol to ultrasonically clean it for 15 minutes, and blow dry it with nitrogen for later use;

[0150] (2) The cleaned ITO substrate was surface treated with plasma for 6 min; then fixed on a spin coater, spin coated with PEDOT:PSS solution at a speed of 4000 rpm for 40 s, and heated and annealed at 150°C for 15 min;

[0151] (3) Spin coating the prepared TFB solution on the above substrate at 2000 rpm for 40 seconds, and heating and annealing at 150° C. for 10 minutes;

[0152] (4) A quantum dot layer (QDs) is continuously constructed on the above substrate, and a mixed solution of red quantum dots and photosensitive crosslinker A is prepared, wherein the solvent is chlorobenzene and the CdSe / Cd 1-x Zn x The concentration of Se / ZnSe red quantum dots was 10 mg / mL, and the concentration of photosensitive crosslinker A was 1 mg / mL. The film was spin-coated at 2000 rpm for 60 s. After that, the film was selectively irradiated with 365 nm ultraviolet light using a mask. The irradiation dose was 300 mJ / cm 2, so that the ligands on the surface of the quantum dots are fully cross-linked, and the areas where no cross-linking reaction occurs are dynamically eluted using chlorobenzene solvent (50-100μL chlorobenzene is dripped on the top of the wafer at a speed of 2000rpm) to obtain a patterned film, which is heated and annealed at 80°C for 10min; when conducting electrical performance test and evaluation, the difference in the construction of the light-emitting layer is that no mask is used, and the entire film is illuminated to avoid the influence of excessive leakage current, thereby better reflecting the impact of this cross-linking patterning method on the optoelectronic properties of the device.

[0153] (5) ZnO ethanol solution was spin coated at 2000 rpm for 40 s and heated and annealed at 80 °C for 20 min;

[0154] (6) Place the above device in a high vacuum evaporation chamber (pressure ≤ 1×10 -6 mbar), thermally deposited 80nm metal Al electrode;

[0155] (7) Use the power supply to connect the positive and negative electrodes of the device and light up the actual QLEDs pattern, such as Fig.14 The rectangular array shown in B has dimensions of 10 μm × 50 μm.

[0156] (8) Evaluate the electrical performance of the device, encapsulate the device with UV-curable resin, and use a combination of QE-PRO spectrometer and Keithley 2400 in an air atmosphere to test device parameters and performance such as QLEDs brightness, current density, and emission wavelength. Fig.14 C in the middle is the current density and luminous brightness vs. voltage curve of the constructed patterned red QLEDs device; the current density is about 700mA / cm 2 , luminous brightness reaches 12000cd / m 2 ; Fig.14 D in the figure is the wavelength of the patterned QLEDs at different voltages of 2, 3, 4, and 5V, all at 620nm. The actual test shows that the square pixels of the QLEDs are lit (see Fig.14 The area is 7.25mm 2 .

[0157] Test Example 6 Construction of InP-based QLEDs light-emitting display device and evaluation of corresponding electrical performance

[0158] This test example provides a patterned InP-based-QLEDs light-emitting display device construction and corresponding electrical performance evaluation. The InP / ZnS red quantum dots in Example 1 are selected. The light-emitting display device structure is the same as that in Test Example 5, ITO / PEDOT:PSS / TFB / QDs / ZnO / Al structure. The specific implementation steps are as follows:

[0159] (1) Take a clean ITO substrate, use commercial glass alkaline detergent to ultrasonically clean it for 15 minutes, then use deionized water to ultrasonically clean it for 15 minutes, repeat twice, then use anhydrous ethanol to ultrasonically clean it for 15 minutes, and blow dry it with nitrogen for later use;

[0160] (2) The cleaned ITO substrate was surface treated with plasma for 20 min; then fixed on a spin coater, spin coated with PEDOT:PSS solution at 3000 rpm for 30 s, and heated and annealed at 150°C for 15 min;

[0161] (3) Spin coating the prepared TFB solution on the above substrate at 3000 rpm for 40 seconds, and heating and annealing at 150° C. for 10 minutes;

[0162] (4) A quantum dot layer (QDs) was continuously constructed on the above substrate, and a mixed solution of red quantum dots and photosensitive crosslinker A was prepared. The solvent was octane, the concentration of red quantum dots in the solution was 20 mg / mL, and the concentration of photosensitive crosslinker A was 1 mg / mL. The solution was spin-coated at a speed of 2000 rpm for 60 s, and the entire film was cross-linked by 365 nm ultraviolet light with a light dose of 100 mJ / cm 2 , dynamic elution was performed using octane solvent, and heating annealing was performed at 80 °C for 10 min;

[0163] (5) ZnO ethanol solution was spin coated at 2000 rpm for 40 s and heated and annealed at 80 °C for 20 min;

[0164] (6) Place the above device in a high vacuum evaporation chamber (pressure ≤ 1×10 -6 mbar), thermally deposited 100nm metal Al electrode;

[0165] (7) Evaluate the electrical performance of the device, encapsulate the device with UV-curable resin, and use a combination of QE-PRO spectrometer and Keithley 2400 in an air atmosphere to test device parameters and performance such as QLEDs brightness, current density, and emission wavelength. Fig.14 E in the figure is the current density and luminous brightness vs. voltage curve of the constructed patterned red InP-based QLEDs device; the current density is about 600 mA / cm 2 , the luminous brightness reaches 35000cd / m 2 ; Fig.14 F in the middle is the emission wavelength of the patterned QLEDs at different voltages of 2, 3, 4, and 5 V, all at 620 nm.

[0166] Test Example 7 Changes in fluorescence quantum yield before and after patterning

[0167] This test example investigates the change in fluorescence quantum yield of a quantum dot before and after patterning under the action of a photosensitive crosslinker. Compared with Test Example 2, the photosensitive crosslinker A is changed to C, the patterning conditions are changed to the concentration of lnP / ZnS red quantum dots in the solution is 30 mg / mL, the concentration of photosensitive crosslinker C is 2 mg / mL, and the light dose is 300 mJ / cm 2 , illumination time 30s, the results are as follows Fig.15 As shown, the quantum yield of the initial film without treatment of quantum dots is normalized to 100%, and after patterning using photosensitive crosslinker C in air, the red lnP / ZnS quantum dots have a good yield retention of 80%.

[0168] Test Example 8: Changes in fluorescence lifetime before and after patterning

[0169] This test example investigates the change in fluorescence lifetime of a quantum dot before and after patterning under the action of a photosensitive crosslinker. Compared with Test Example 3, the photosensitive crosslinker A is changed to C, the patterning conditions are changed to the concentration of lnP / ZnS red quantum dots in the solution is 30 mg / mL, the concentration of photosensitive crosslinker C is 2 mg / mL, and the light dose is 300 mJ / cm 2 , illumination time 30s, the results are as follows Fig.16 As shown, the patterning step does not reduce the average fluorescence lifetime of the quantum dots themselves. The average fluorescence lifetime of the initial film without quantum dots is 31.12ns, and the average fluorescence lifetime of the final patterned film is 28.83ns.

[0170] Comparative Example 1

[0171] This comparative example provides a method for preparing a patterned quantum dot film. Compared with the quantum dot patterning methods in Examples 1, 3, and 4, the difference in this comparative example is that the photosensitive crosslinker is replaced by 3,3'-(4,4'-perfluorobutane-1,4-diyl)bis(4,1-phenylene)bis(3-trifluoromethyl)-3H-diacridine from the provided A, B, and C, and the molecular formula is as follows:

[0172]

[0173] The molecular synthesis method refers to the existing literature "Shaoyong Lu, et al. Beyond a Linker: The Role of Photochemistry of Crosslinkers in the Direct Optical Patterning of Colloidal Nanocrystals. Angew. Chem. Int. Ed., 2022, 61, e202202633", and the preparation method includes the following steps:

[0174] At 0°C, under argon conditions, a triethylamine solution (3.06 mL) was added dropwise to a dichloromethane solution (21 mL) of 3,3'-((perfluorobutane-1,4-diyl)bis(4,1-phenylene))bis(3-(trifluoromethyl)diaziridine) (2.1 g) over 10 minutes, and iodine (2.04 g) was added to the resulting mixture three times, and stirring was continued at 0°C for 2 hours. The reaction mixture was diluted with dichloromethane (60 mL) and transferred to a separatory funnel, and the organic layer was washed with water, a saturated sodium thiosulfate solution, water and brine, and dried over sodium sulfate. The organic layer was purified by silica gel column chromatography to obtain the desired bright white crystalline cross-linked molecule.

[0175] The same process was carried out in air. In this comparative example, a portion of the exposed InP / ZnS quantum dot film was immersed in toluene, but no pattern was seen (e.g. Fig.17 The reason is that: after ultraviolet light exposure, 3,3'-(4,4'-perfluorobutane-1,4-diyl)bis(4,1-phenylene)bis(3-trifluoromethyl)-3H-diacridine molecules generate singlet carbene intermediates. In the air, the singlet carbene is easily converted to a triplet state and reacts with oxygen to consume the generated intermediate, and fails to undergo cross-linking through the quantum dot surface ligands. However, the A, B, and C molecules designed by the present invention inhibit the process of the intermediate singlet state to the triplet state due to the introduction of electron-donating groups. Even in the air, the singlet intermediates can efficiently undergo cross-linking with the surface ligands to achieve patterning of the quantum dot material.

[0176] Comparative Example 2

[0177] This comparative example provides a patterning effect of quantum dots under the action of different photosensitive crosslinking agents. Compared with the quantum dot patterning conditions in Example 4, photosensitive crosslinking agent C is used in air. The difference is that the ultraviolet light dose is increased from 300mJ / cm 2 Replaced with 50mJ / cm 2 , the partially exposed red lnP / ZnS quantum dot film was immersed in toluene, but no pattern was seen (e.g. Fig.18 As shown), compared with the photosensitive crosslinker A in Example 1 at 50mJ / cm 2 The reason for patterning is that the photosensitive crosslinker A has a large molar absorption coefficient at a wavelength of 365nm and has a higher ultraviolet light utilization rate. The tridentate crosslinking sites in the photosensitive crosslinker A also make the crosslinking reaction more efficient.

Claims

1. A method for patterning a quantum dot thin film, comprising the following steps: (1) Mixing quantum dots with a photosensitive crosslinker to form a thin layer; (2) performing patterned exposure treatment on the thin layer to obtain a patterned quantum dot thin film; Wherein, the surface of the quantum dots has ligands containing carbon-hydrogen bonds; The photosensitive crosslinking agent has a structure shown in Formula I: In formula I, R1 is an electron-donating group; n≥2; and X is a group that does not affect the formation of a singlet intermediate.

2. The method for patterning a quantum dot thin film according to claim 1, wherein: In formula I, R1 contains one or more structures selected from the group consisting of alkylamino, alkoxy, ether, acyloxy, amide, alkyl, alkylene, carboxymethyl, and phenyl; n is 2, 3, or 4; X is selected from the group consisting of H, halogen, hydroxy, alkyl and its derivatives, alkoxy and its derivatives, amino, and nitrile; Preferably, X is selected from -Cl, -F, -OH, -H, -CH3, -CF3, -OCH3, -NH2 or -CN; Preferably, R1 contains one or more structures of phenyl, ether, and alkylene; n is 2, 3, or 4; X is selected from -CF3; Preferably, the photosensitive crosslinking agent has a carbon atom number of 1-100 and a molecular weight of 100-10000; Preferably, the photosensitive crosslinking agent is selected from One or a combination of two or more.

3. The method for patterning a quantum dot thin film according to claim 1, wherein: The material of the quantum dots includes one or a combination of two or more of II-VI compounds, III-V compounds, IV-VI compounds, I-III-VI compounds, and perovskite nanocrystals; Preferably, the quantum dots are core-shell structured quantum dots; Preferably, the II-VI group compounds include CdSe, CdS, CdTe, Cd x Se 1-x S, Cd x Se 1-x Te, ZnO, ZnSe, ZnS, ZnTe, Zn x Se 1-x S, Zn x Se 1-x Te, Cd x Zn 1-x Se, Cd x Zn 1-x S, Cd x Zn 1-x Te, HgSe, HgS, HgTe, Hg x Cd 1-x Se, Hg x Cd 1-x S, Hg x Cd 1-x One or a combination of two or more of Te, wherein 0<x<1; Preferably, the III-V group compound includes one or a combination of two or more of InP, InAs, InSb, InN, GaP, GaAs, GaSb, GaN, AlP, AlAs, AlSb, and AlN; Preferably, the IV-VI group compound includes PbS, PbSe, PbTe, Pb x Se 1-x S, Pb x Se 1-x Te, SnS, SnSe, SnTe, Sn x Se 1-x S, Sn x Se 1-x One or a combination of two or more of Te, wherein 0<x<1; Preferably, the I-III-VI group compound includes one or a combination of two or more of CuInS2, CuInSe2, and AgInS2; Preferably, the perovskite nanocrystals include one or a combination of two or more of CsPbY3, CH3NH3PbY3, FAPbY3, MAPbY3, wherein Y is selected from Cl, Br or I.

4. The method for patterning a quantum dot thin film according to claim 1, wherein: The number of carbon atoms of the surface ligands of the quantum dots is 3-30; Preferably, the main chain of the surface ligand of the quantum dot contains a carbon-hydrogen bond; Preferably, the surface ligands of the quantum dots contain one or more structures of thiol, carboxylic acid, amine, phosphine, and phosphonic acid; Preferably, the surface ligands of the quantum dots include one or a combination of two or more of oleylamine, oleic acid, octadecylamine, 1-dodecanethiol, trioctylphosphine, and octadecylphosphonic acid.

5. The method for patterning a quantum dot thin film according to claim 1, wherein: In step (1), quantum dots and a photosensitive crosslinker are mixed in a solvent to obtain a solution, and the solution is formed into a thin layer; wherein the concentration of quantum dots in the solution is 5-1000 mg / ml, and the mass concentration ratio of quantum dots to the added photosensitive crosslinker is 1:(0.01-1); Preferably, the solvent of the solution is selected from one or a combination of two or more of toluene, chlorobenzene, n-hexane, n-octane, n-heptane, cyclohexane, dichloromethane, chloroform and tetrahydrofuran; Preferably, the molar absorption coefficient of the photosensitive crosslinking agent at the exposure treatment wavelength is 10 cm -1 M -1 Up to 10 6 cm -1 M -1 .

6. The method for patterning a quantum dot thin film according to claim 1, wherein: Each step of the quantum dot film patterning method is implemented in air, nitrogen or argon respectively; Preferably, in step (2), the wavelength of the exposure treatment is 100-500 nm, and the light dose is 1-5000 mJ / cm 2 ; Preferably, after the thin layer is exposed, an elution solvent is used to remove the raw materials that have not undergone cross-linking. The elution solvent is a non-polar solvent, preferably including one or a combination of two or more of toluene, chlorobenzene, n-hexane, n-octane, n-heptane, cyclohexane, dichloromethane, chloroform, and tetrahydrofuran.

7. A patterned quantum dot film produced by the quantum dot film patterning method according to any one of claims 1 to 6.

8. A photoelectric device, the structure of which comprises an anode, a cathode, and a quantum dot light-emitting layer, wherein: The quantum dot light-emitting layer is the patterned quantum dot film according to claim 7 or is prepared by the quantum dot film patterning method according to any one of claims 1 to 6; Preferably, the quantum dot light-emitting layer is located between the cathode and the anode, and the materials of the anode and the cathode are independently selected from metals or carbon materials; the metal is selected from one or a combination of two or more of Al, Ag, Au, Cu, Mo, Mg, Ba, and Ca, and the carbon material is selected from one or a combination of two or more of carbon nanotubes, graphite, graphene, and carbon fibers.

9. The optoelectronic device according to claim 8, wherein: The structure of the photoelectric device further comprises an electron injection layer, a hole injection layer, an electron transport layer, and a hole transport layer. The electron injection layer and the electron transport layer are located between the cathode and the quantum dot light-emitting layer, the electron injection layer is close to the cathode, and the electron transport layer is close to the quantum dot light-emitting layer; the hole injection layer and the hole transport layer are located between the anode and the quantum dot light-emitting layer, the hole injection layer is close to the anode, and the hole transport layer is close to the quantum dot light-emitting layer. Preferably, the material of the electron injection layer includes one or a combination of two or more of alkali metal halides, alkali metal organic complexes, organic phosphorus oxides, organic thiophosphine compounds, and organic selenophosphine compounds; Preferably, the material of the electron transport layer includes a single metal oxide and / or a doped metal oxide, wherein the single metal oxide is selected from one or a combination of two or more of ZnO, ZrO2, SnO2, BaO, TiO2, and Ta2O3; the doped metal oxide is the single metal oxide doped with one or more elements of Al, Li, Ga, Mg, Sn, In, F, and Cl; Preferably, the material of the hole injection layer is selected from one or more of poly(3,4-ethylenedioxythiophene), poly(styrenesulfonic acid), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, 4,4',4'-tri(2-naphthylphenylamino)triphenylamine, 1,4,5,8,9,12-hexaazatriphenyl-2,3,6,7,10,11-hexanitrile, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, NiO, MoO2, WO3, CrO3, CuO, MoS2, MoSe2, WS2, CuS, and WS2; Preferably, the material of the hole transport layer is selected from poly(3-hexylthiophene-2,5-diyl), poly(9-vinylcarbazole), poly[[(2,4-dimethylphenyl)imino]-1,4-phenylene(9,9-dioctyl-9H-fluorene-2,7-diyl)-1,4-phenylene], poly(9,9-dioctylfluorene-2,7-diyl), poly[bis(4-phenyl)(4-butylphenyl)amine], poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-tert-butylphenyl)diphenylamine)], poly[9,9-dioctylfluorene -bis-N,N-(4-butylphenyl)-bis-N,N-phenyl-1,4-phenylenediamine], tris[4-(carbazole-9-yl)phenyl]amine, 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, poly(3,4-ethylenedioxythiophene), poly(styrenesulfonic acid), graphene, NiO, WO3, CuI, CuSCN, CuO, CuInS2, GaN, C60, MoO3, V2O5, CrO3, or a combination of two or more thereof.

10. The optoelectronic device according to claim 8 or 9, wherein: The photoelectric device is an array photoelectric device.

Citation Information

Patent Citations

  • Photoresist-free photoinduced patterning method of quantum dot film

    CN111781803A

  • Method for improving performance of electroluminescent device by modifying indium phosphide quantum dots on interface of thiol compound

    CN114242923A

  • Method and apparatus for non-destructive lithographic patterning of quantum dots

    CN114839835A

  • Quantum dot light-emitting diode and preparation method therefor

    WO2022016822A1